A Report of Post-Concussion Syndrome in Post-Moderate Traumatic Brain Injury Patients - Yuanita Eka Maulinda; Endiyono Endiyono (Proceedings Series on Health & Medical Sciences, 2021)
Traumatic brain injury is the most common injury, especially in motorcycle riders who do not wear helmets or those who wear unsafe helmets. This injury can be fatal and result in death, but it can also be healed without any sequelae or with varying sequelae. The type of sequelae that commonly occurs after a traumatic brain injury is Post-Concussion Syndrome. Moreover, it has some symptoms such as headaches, impaired concentration, tiredness, anxiousness, dementia, and impaired cognitive function. Based on its onset, Post-Concussion Syndrome is classified into 3: acute (the symptoms appear less than one month after injury), subacute (the symptoms appear from 1 to 12 months), and chronic (the symptoms appear more than a year). The purpose of this research is to provide an overview of symptoms in cases of Post Concussion. Syndrome that occurs after 6 months after moderate head injury.The design of this study used a case report method in order to report cases in detail through interviews and direct observation on respondents. The results of Rivermead, Galveston Orientation and Amnesia Tests conducted 6 months after moderate traumatic brain injury, indicated that respondents experienced Post-Concussion Syndrome and Retrograde Amnesia. The conclusion of Post-Concussion Syndrome experienced by the respondents was subacute with several symptoms such as headache, dementia, impaired concentration, anxiousness, and memory loss of before injury.